Gugus Konsonan Bahasa Jawa Dialek Surabaya - Dian Rachmawati; Sri Diharti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
This study discusses consonant clusters in the Javanese dialect of Surabaya. A consonant group is two or more consonants that are consecutive in one syllable. The method used in this study, namely a qualitative descriptive method obtained from speakers of the Javanese dialect of Surabaya. The data collection used in this study, namely the proficient method using basic techniques in the form of fishing rods. This technique is used to provoke informants to bring up the expected linguistic symptoms. The results of this study showed that consonant clusters in Javanese dialect of Surabaya can occur at two consonants and three consonants. Furthermore, in this research, it is shown that there are consonant clusters in Javanese dialect of Surabaya, but not in Indonesian consonant clusters.